Cefmetazole, flomoxef, and meropenem are effective against planktonic cells but not biofilms of extended-spectrum β-lactamase-producing Escherichia coli - Nami Hatayama; Yoshinori Sato; Rika Tahira; Toki Hori; Shigeru Tansho-Nagakawa; Yasuo Ono; Yusuke Yoshino (BMC Microbiology)
Abstract Background Extended-spectrum β-lactamase (ESBL)-producing Escherichia coli is a potential  public health threat through its spread into the environment. Cefmetazole (CMZ) and flomoxef (FMOX) are highly effective alternatives to meropenem (MEM) for the management of ESBL-producing E. coli infections. However, their antimicrobial effects on biofilms remain unclear. Therefore, this study aimed to elucidate the inhibitory and bactericidal effects of CMZ, FMOX, and MEM on the biofilms formed by ESBL-producing E. coli. Methods Three ESBL-producing E. coli clinical isolates with biofilm-forming abilities (strains F6, F11, and U3) were used in the present study. Biofilm formation and viability assay kits were used to assess the inhibitory and bactericidal effects of these antibiotics on the biofilm-dispersed and biofilm cells of these strains. Scanning electron microscopy (SEM) was used to acquire images of the biofilms treated with these antibiotics. Results CMZ and MEM exerted significant inhibitory effects on the growth of biofilm-dispersed cells of all three strains at 1 × minimum inhibitory concentration (MIC). FMOX also exerted significant inhibitory effects on the growth of biofilm-dispersed cells of F11 strain at 1 × MIC; however, it exerted inhibitory effects on the growth of biofilm-dispersed cells of strains F6 and U3 in a concentration-dependent manner. CMZ, FMOX, and MEM exerted different bactericidal effects on biofilm-dispersed cells. CMZ exerted significant inhibitory effects on biofilm formation in all strains at 1 × MIC, whereas MEM exerted significant inhibitory effects on biofilm formation in the F6 and F11 strains at 1 × MIC. FMOX induced biofilm formation in F6 and U3 strains at concentrations between 1 × and 4 × MICs. Notably, CMZ, FMOX, and MEM did not exert bactericidal effects on the biofilm cells of any strain. SEM analysis revealed the induction of bacterial filamentation in the presence of CMZ and FMOX and spheroplast formation in the presence of MEM at 1 × MIC. Conclusions CMZ, FMOX, and MEM exhibited varying antimicrobial effects against ESBL-producing E. coli biofilms. Notably, FMOX may increase biofilm formation by inducing strong morphological changes. CMZ and FMOX are effective alternatives to MEM for ESBL-producing E. coli infections; however, their use requires the consideration of biofilm formation.